INDEKS GLIKEMIK DAN BEBAN GLIKEMIK TEMPE KEDELAI DENGAN SUBSTITUSI BIJI LAMTORO (Leucaena leucocephala) - Titania Pramudyawardhani Darmawan (2023)
The prevalence of Type 2 Diabetes Mellitus (T2DM) in Indonesia continues to increase every year. Consuming food with a low glycemic index (GI) and glycemic load (GL) can help control T2DM. Tempeh is widely consumed by Indonesian people. Soybean tempeh with lamtoro seed substitution is assumed to have a low GI due to the high antioxidant and dietary fiber content in lamtoro seed. The purpose of this study was to determine the GI and GL values of lamtoro seed substitution of soybean tempeh. This study used a true experimental study design with 10 healthy adult subjects divided into 2 groups. The control group was given a 25 grams of pure glucose. The treatment group consisted of 3 tempeh formulas with a comparison of soybean and lamtoro seed: 60%:40% (F1), 50%:50% (F2), and 40%:60% (F3). The results of the anova test showed that there were significant differences (p<0.05) in the glycemic response and AUC size between the control and treatment groups. The GI value of tempeh is 10.56 (F1); 9.24 (F2); and 6.04 (F3). The GL value of tempeh is 0.44 (F1); 0.35 (F2); and 0.21 (F3). The GI and GL values of tempeh is included in the low category and tend to decrease along with the addition of lamtoro seed composition.